Improve Quality Of Public Opinion In Website Using Blockchain Technology - Munandar, Galih Mahardika; Ma’arif, Imam Samsul (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The unemployment rate in Indonesia is quite high, where the average value in Indonesia is 18%, the largest among Cambodia, Nigeria, and lower-middle-class countries, which show an average of 12%. The high unemployment rate is caused by the level of motivation of students to continue working, studying or participating in competency training with a lack of interest. To increase students' interest, it is necessary to have a large number of critical communications to arouse students' enthusiasm and motivation. The method used is qualitative and quantitative where to design the system design and system validation, the technique used is the System Development Life Cycle Waterfall. The results obtained by the Heuristic Evaluation stated that not many things needed to be improved for the system that was created and the SUS (System Usability Score) stated that it was good with a minimum score of 68 given by 5 experts. The Blockchain system can already be run or applied to the wider community. Keywords: Blockchain, Heuristic Evaluation, System Usability Scale, Siswa, System Development Cycle